Laparoscopic Cholecystectomy; It’s Complications and Causes of Conversion to Open Cholecystectomy. - Al-Dhahiry, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: The laparoscopic cholecystectomy is the gold standard for treating the symptomatic cholelithiasis. Conversion is sometimes necessary due to finding unexpected pathology,intraoperative complications or unexpected technical errors .Objectives: The aims of this study were to determine the complications and the predictive factors of conversion in patients undergoing laparoscopic cholecystectomy for various indications in elective and acute settings in a general hospital in order to reduce the incidence rates of both , complications and  conversion of laparoscopic cholecystectomy to the open technique .Patients and Methods: This is a prospective study included 128 patients [their ages ranged from18 -65 years; the mean =39.60 ± 11.37 SD years].Female patients were 111 (86.7 ) ,male patients were 17 (13.3 % ) . These patients underwent a laparoscopic cholecystectomy in AL-Karama Teaching Hospital / College of Medicine / Wasit University-Iraq,from April 2011 till December 2012. Recorded data were sex, age, indications for laparoscopic cholecystectomy , complications, conversion to the open technique , reasons of conversion, co- morbidity , length of the hospital stay and 30- day mortality.Results: The intraoperative complications were; bleeding from the cystic artery in 9 patients (7.03 %), perforation of the gallbladders in17 patients (13.28% ) and spillage of the stones from cystic duct stump in12 patients( 9.37% ).All these complications were successfully treated laparoscopically.This study has no postoperative complications during follow-up period . Conversion from a laparoscopic cholecystectomy to an open cholecystectomy was performed for 7 patients ( 5.49 % ). The reasons for conversion were ; dense fibrosis of Calot’s triangle in two patients ( 1.56 % ) and one patient(0.78 % ) for each of the following pathologies : cholecystoduodental fistula ,postoperative adhesions , impacted stone in the cystic duct , Mirrizzi’s syndrome and incidental CBD stone.The intaoperative findings and postoperative histopathologic diagnoses were: 114 patients( 89.1 % ) with chronic calculous cholecystitis, 5 patients ( 3.9 % ) with acute calculous cholecystitis, 5 patients( 3,9 % )  with empyema of the gall bladder, 4 patients ( 3.1 % ) with mucocele of the gall bladder .There was no mortality in this study .                                                                                                                        Conclusions: In this study,there were simple complications being laparoscopically treated .Male gender, age older than 50 years that were associated with dense fibrosis of Calot’s triangle , postoperative upper abdominal adhesions,cholecystoduodenal fistula Mirrizi’syndrome ,impaced stones in the cystic duct and incidental CBD stone were the main factors of conversion .